Systematic review of immunosuppressant guidelines in the COVID-19 pandemic - Fenella Barlow-Pay; Thura Win Htut; Mina Khezrian; Phyo Kyaw Myint (SAGE Publishing, 2021)
Aims: Individuals taking immunosuppressants are at increased susceptibility to viral infections in general. However, due to the novel nature of the COVID-19, there is a lack of evidence about the specific risks of the disease in this patient group. This systematic review aims to summarize the current international clinical guidelines to highlight areas where research is needed through critical appraisal of the evidence base of these guidelines. Methods: We conducted a systematic review of clinical practice guidelines about the usage of immunosuppressants during the COVID-19 pandemic. Electronic databases including MEDLINE and the websites of relevant professional bodies were searched for English language guidelines that were published or updated between March 2020 and May 2020 in this area. We assessed the quality and consistency of guidelines. The evidence base underpinning these guidelines was critically appraised using GRADE criteria. Results: Twenty-three guidelines were included. Most guidelines ( n  = 15, 65.2%) informed and updated evidence based on expert opinion. The methodological quality of the guidelines varied, ranging from 'very low' to 'moderate'. Guidelines consistently recommended that high-risk patients, including those who are taking high doses of steroids for more than a month, or a combination of two or more immunosuppressants, should be shielding during the outbreak. Most guidelines stated that steroids usage should not be stopped abruptly and advised on individualized risk-benefit analysis considering the risk of the effect of COVID-19 infection and the relapse of the autoimmune condition in patients. Discussion: Clinical practice guidelines on taking immunosuppressants during the COVID-19 outbreak vary in quality. The level of evidence informing the available guidelines was generally low. Given the novel nature of COVID-19, the guidelines draw on existing knowledge and data, refer to the use of immunosuppressants and risks of serious infections of other aetiologies and have extrapolated these to form their evidence base.